Amino Acid Composition in Various Types of Nucleic Acid-Binding Proteins - Bartas, Martin; Červeň, Jiří; Guziurová, Simona; Slychko, Kristyna; Pečinka, Petr (International journal of molecular sciences, 2021)
Nucleic acid-binding proteins are traditionally divided into two categories: With the ability to bind DNA or RNA. In the light of new knowledge, such categorizing should be overcome because a large proportion of proteins can bind both DNA and RNA. Another even more important features of nucleic acid-binding proteins are so-called sequence or structure specificities. Proteins able to bind nucleic acids in a sequence-specific manner usually contain one or more of the well-defined structural motifs (zinc-fingers, leucine zipper, helix-turn-helix, or helix-loop-helix). In contrast, many proteins do not recognize nucleic acid sequence but rather local DNA or RNA structures (G-quadruplexes, i-motifs, triplexes, cruciforms, left-handed DNA/RNA form, and others). Finally, there are also proteins recognizing both sequence and local structural properties of nucleic acids (e.g., famous tumor suppressor p53). In this mini-review, we aim to summarize current knowledge about the amino acid composition of various types of nucleic acid-binding proteins with a special focus on significant enrichment and/or depletion in each category.
Keywords: DNA vazebné proteiny; transportní proteiny; cruciform; amino acid composition; sekvence aminokyselin; nukleoproteiny; zinkové prsty; i-motif; DNA; lidé; Zinc Fingers; Z-DNA; Nucleic Acid Conformation; RNA; Amino Acid Sequence; konformace nukleové kyseliny; G-kvadruplexy; protein binding; Carrier Proteins; Leucine Zippers; G-Quadruplexes; Z-RNA; Nucleoproteins; triplex; G-quadruplex; DNA-Binding Proteins; leucinové zipy; DNA, Z-Form; Humans